Deconstruction of Emotional Discourse in the Novel Gullo Gullo by Miodrag Bulatović - Đurišić-Bečanović, Tatjana (Poznańskie Studia Slawistyczne, 2015)
The paper deals with a detailed analysis of the characteristics of emotional discourse, organized in a literary text, specifically in the novel Gullo Gullo by Miodrag Bulatovic. Since expressing of emotions can be verbal and non-verbal, both codes relating the organization of emotional discourse have been activated. In the analysis of literary coded emotional discourse the author had to consider two-instance system of art. The fiction as a basic distinctive feature of a literary text has a crucial influence on the emotional semiosis resulting in producing emotional meaning. That process has always been influenced by various features of poetic language and its combinatorics, which are significantly different from encoding in real chronotope expressed in native language forms, governed by quite different rules of expressing emotions and transferred by the people and not the literary structure. Since the fact that disorders of phatic function of a language, communication and culture, are defined as major agents of the process in question their accepted values novels written by Miodrag Bulatovic, the author points out the importance of carnival, grotesque, pornography and satire which have been used as the main degradation processes of the canonized cultural and communication patterns in the novel, whose destructive operation inevitably affects the emotional discourse.